Factibilidad para la creación de una microempresa procesadora de miel y polen de abeja en el cantón Chone, provincia de Manabí - Sánchez Macías, Dora Valentina (2021)
The purpose of this research work was to develop a feasibility study for the creation of a honey and bee pollen processing microenterprise in the canton Chone, Manabí province. The market study was carried out through the survey as the main technique, which was applied to the population of the canton Chone, belonging to the socioeconomic strata A, B, C+ and C-, obtaining as a result 61,70 % acceptance in bee honey and 10,30 % in bee pollen. In the engineering of the project, the product was characterized by bromatological and microbiological analyses, and the need for raw materials, inputs, materials, equipment, infrastructure and labor required for the operational phase was planned. In the environmental impact study, Leopold's matrix was used as a model for the analysis of environmental impacts, by which positive impacts were identified in the construction, operation and abandonment stages of the plant, due to the generation of jobs aimed at the inhabitants of the site, in the same way, low-magnitude negative environmental impacts were identified that can be mitigated by applying the proposed preventive measures. Finally, the financial economic viability of the project was determined by the financial indicators, as a VAN of $273714,42 and a TIR of 51,00 % were obtained, which exceeds the discount rate of 10,50 %.